Knowledge about age-related eye diseases in the general population in Germany - Terheyden, Jan H.; Fink, David; Mercieca, Karl; Wintergerst, Maximilian W. M.; Holz, Frank G.; Finger, Robert P. (BMC public health, 2024)
Background: With a rising prevalence of age-related eye diseases, prevention and early diagnosis of these conditions are key goals of public eye health. Disease-related knowledge in the general public supports these goals but there is little data available. Thus, we have assessed knowledge of cataract, glaucoma, age-related macular degeneration (AMD) and diabetic eye disease in the German adult general population in a cross-sectional study and identified target groups for health education interventions. Methods: Knowledge assessment content was identified based on a literature review, expert input, and a list of items was generated after a qualitative selection process. The resulting 16-item instrument (4 items per condition) was administered to 1,008 participants from a survey panel, demographically representative of the adult German population. Test properties were evaluated based on a Rasch model and multiple correspondence analysis (MCA). Binary-logistic regression analysis was performed to investigate associations with age, sex, education level, employment status, marital status, income, reported health status, visual difficulties, and recent general practitioner (GP) and ophthalmologist consultations. Results: Replies were correct for a median of 9 out of 16 (range 2 – 16) items, which differed between conditions (p < 0.0001). Most responses were correct for cataract items (median: 3 / 4) and least were correct for AMD items (median: 2 / 4). 27%, 9%, 1% and 19% of respondents replied correctly to all cataract, glaucoma, AMD and diabetic eye disease-related items, respectively. Rasch analysis suggested an adequate targeting of items and in MCA, no evidence of multidimensionality was present. Older age, being retired, decreased general health and recent GP or ophthalmology consultations were significantly associated with more knowledge about common eye conditions (p ≤ 0.005). GP or ophthalmology consultations remained significant in a multivariable model (p ≤ 0.011). Conclusions: Knowledge gaps regarding eye health are considerable in the German general population and should therefore be addressed in educational interventions targeting the public. Special attention when designing such campaigns needs to be paid to infrequent users of the healthcare system. Knowledge of AMD seems to be poorer compared to other eye conditions.
Gesehen am 27.05.2024